IMPLEMENTASI DATA KEUANGAN DENGAN ZAHIR ACCOUNTING PADA PT. ANUGERAH ANALISIS SEMPURNA - Susan Rachmawati; Nurjanah Nurjanah (Politeknik Negeri Batam, 2017)
With the number of data transactions that occur, if data collection is done manually much time wasted for financial data processing. Because many stages to be done to be able to produce financial statements. The resulting data is not necessarily accurate and appropriate. Accounting applications have been created to facilitate in making decisions on the business run. The use of computer accounting applications is very efficient and effective for a businessman or a trader in running his business. Processing financial data that only live input transaction data alone, can produce the desired report for decision making. By using Zahir Accounting the ease given is indeed designed as simple as possible so that users can easily understand the features provided. In the processing of data that has been inputted directly form the journal and also the financial statements. So it is very effective and efficient if using computer accounting application Zahir Accounting 5.1 version either beginners or professional.